Sex education as a public policy with a gender perspective in La Rioja Province, 2019-2022 (Papeles, 2023)
This paper presents the interventions developed by La Rioja's provincial government since Sexual Education National Law was approved (ESI in Spanish) in 2006. First of all, a normative and institutional evaluation of the implementation of ESI in the province under the executive responsibility of La Rioja’s Ministry of Education is presented. Secondly, it describes the educational and cultural public policies that have been enacted in La Rioja province. Finally, it considers the obstacles that still need to be overcome as well as the opposition that emerged. Some public policies, such as ESIarte or "Chaya es amor por tu gente" are presented as a way of establishing a link between the local culture and its transformation since the ESI onwards. Using a descriptive approach serves as a starting point for understanding changes and resistance that different parts of the nation, in this case, the northwest of Argentina, have experienced since the implementation of the already-mentioned national law.
Keywords: Sex education; public policies with a gender perspective; La Rioja Province; Ministry of Education